Mechanical design of automatic beach cleaner / Muhammad Qaiyim Almunawwar Ahmad Zawave and Nurulnatisya Ahmad - Ahmad Zawave, Muhammad Qaiyim Almunawwar; Ahmad, Nurulnatisya (School of Mechanical Engineering, 2023)
The aim for this project is to design the machine that capable to help clean up on the beach more efficiently without using a lot of energy and reduces the cost that is affordable for everyone. The method of operating this machine is pushes and pulls mechanism because it has a wheel. Rather than picking up trash on the beach manually, this machine will pick it up automatically without digging into the sand and collecting one by one the trash that found on the beach. The design of the machine should be suitable on sandy place like on the beach because it has a mechanism that separates the sand and trash. The machine also will be design with the right size.